Gankyrin-mediated interaction between cancer cells and tumor-associated macrophages facilitates prostate cancer progression and androgen deprivation therapy resistance - Guang Peng; Chao Wang; Hongru Wang; Min Qu; Keqin Dong; Yongwei Yu; Yuquan Jiang; Sishun Gan; Xu Gao (OncoImmunology)
Increasing evidence reveals that the interaction between tumor cells and tumor-associated macrophages (TAMs) facilitates the progression of prostate cancer, but the related mechanisms remained unclear. This study determined how gankyrin, a component of the 19S regulatory complex of the 26S proteasome, regulates the progression and androgen deprivation therapy (ADT) resistance of prostate cancer through tumor cell–TAM interactions. In vitro functional experiments and in vivo subcutaneous tumor models were used to explore the biological role and molecular mechanisms of gankyrin in prostate cancer cell–TAM interactions. 234 prostate cancer patients were randomly divided into training and validation cohorts to examine the prognostic value of gankyrin through immunohistochemistry (IHC) and statistical analyses, and high gankyrin expression was correlated with poor prognosis. In addition, gankyrin facilitated the progression and ADT resistance of prostate cancer. Mechanistically, gankyrin recruited and upregulated non–POU-domain–containing octamer-binding protein (NONO) expression, resulting in increased androgen receptor (AR) expression. AR then bound to the high-mobility group box 1 (HMGB1) promoter to trigger HMGB1 transcription, expression, and secretion. Moreover, HMGB1 was found to promote the recruitment and activation of TAMs, which secrete IL-6 to reciprocally promote prostate cancer progression, ADT resistance and gankyrin expression via STAT3, resulting in formation of a gankyrin/NONO/AR/HMGB1/IL-6/STAT3 positive feedback loop. Furthermore, targeting the interaction between tumor cells and TAMs by blocking this loop inhibited ADT resistance in a tumor xenograft model. Taken together, the data show that gankyrin serves as a reliable prognostic indicator and therapeutic target for prostate cancer patients.